Effects of Lactococcus lactis from Cyprinus carpio L. as probiotics on growth performance, innate immune response and disease resistance against Aeromonas hydrophila. Issue 93 (October 2019) - Feng, Junchang; Chang, Xulu; Zhang, Yuru; Yan, Xiao; Zhang, Jianxin; Nie, Guoxing
Abstract: In the present study, we reported 18 LAB strains isolated from the intestinal contents of Cyprinus carpio, and their probiotic properties both in vitro and in vivo . The results showed that 9 of them had higher in vitro immunomodulatory properties, effectively survived under acidic (pH 2.5) and bile salt (ranging from 0.1% to 0.5%) conditions, and inhibited the growth of 4 pathogens. Among them, Lactococcus lactis Q-8, Lactococcus lactis Q-9, and Lactococcus lactis Z-2 showed the strongest adhesion abilities and inhibition of pathogen adhesion to mucin. When the fish consumed diets containing these 3 strains (5 × 10 8  CFU/g) for 8 weeks, the weight gain (WG) and specific growth rate (SGR) had significantly ( P  < 0.05) increased, especially with L. lactis Q-8, which had a WG of 231.45%, and SGR of 2.22%. Survival rate in each LAB supplementation group was also significantly higher than that in control group during the feeding period ( P  < 0.05). For the cytokines expression levels in serum, different expression patterns were also observed. Before the infection with Aeromonas hydrophila, L. lactis supplementation significant up-regulated protein levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-12) compared with negative (CK1) group, while these cytokines were significantly lower than those in positive (CK2) group after infection. However, whether infected or not, the expression of anti-inflammatory cytokines (IL-10, TGF-β) were significantly increased in L. lactis Q-8, L. lactis Q-9, and L. lactis Z-2 treatment groups. In conclusion, these 3 L. lactis strains screened from common carp were effective in improving growth, innate immunity and disease resistance. Based on the physiological characteristics in our study, they might be used as potential probiotics in aquaculture. Highlights: Three strains L. lactis Q-8, Q-9 and Z-2 were isolated and screened from common carp intestinal. These three L. lactis strains had higher in vitro immunomodulatory properties. We prepared antibodies against cytokines and detected their expression at protein levels. The single L. lactis -fed carp significantly improved innate immunity and growth performances. L. lactis strains can enhance disease resistance against A. hydrophila in common carp.